1993
DOI: 10.1002/jsfa.2740630309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage temperature on the quality of salted mackerel (Rastrelliger kangurta) and pink perch (Nemipterus japonicus)

Abstract: Dry-salted mackerel and pink perch were stored at two temperatures: ambient (26.8_+ 3.3"C) and 2 5 f 1°C. Changes in moisture content, salt content, water activity (a,), peroxide value (PV), free fatty acid content (FFA), total volatile base nitrogen (TVBN) content, halophilic bacterial count and sensory scores for overall acceptability were studied. Loss of moisture and absorption of salt were considerably higher in the products stored at ambient temperature. The decrease in a, was more pronounced at ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 5 publications
3
15
2
1
Order By: Relevance
“…This may be due to making of ammonical odor by the characteristic strong odor of Chepa. Autolytic enzymes might have caused de-amination of protein resulting in the formation of volatile bases [30,31,32,33]. Although the observed values of the present study are within the acceptable limit as suggested for fishery product by Connell [34].…”
Section: Total Volatile Base Nitrogen (Tvb-n) Content Of Chepa Shutkisupporting
confidence: 39%
“…This may be due to making of ammonical odor by the characteristic strong odor of Chepa. Autolytic enzymes might have caused de-amination of protein resulting in the formation of volatile bases [30,31,32,33]. Although the observed values of the present study are within the acceptable limit as suggested for fishery product by Connell [34].…”
Section: Total Volatile Base Nitrogen (Tvb-n) Content Of Chepa Shutkisupporting
confidence: 39%
“…FFA, resulting from lipid hydrolysis accumulates during frozen storage and accelerates quality deterioration (Saeed and Howell, 2002). Similar results were obtained by Srikar et al, (1993) and Sarma et al, (1998) where the lower increase in FFA may be attributed to the slower rate of lipid oxidation. Similar observations have been recorded for other species.…”
Section: In Tilapia (Oreochromis Niloticus)supporting
confidence: 81%
“…Veciana-Nogue s et al (1997) studied brined anchovy samples obtained from factories and stored at 8±10°C and 20 1°C for 9 months. The highest values were observed with the samples brined at a salt concentration of In a study on the in¯uence of storage temperature on the quality of salted mackerel and pink perch, Srikar et al (1993) found an increase in halophilic counts in all the products during 120 days of storage. Table 3 also shows the total halophile counts.…”
Section: Time (Days)mentioning
confidence: 91%
“…At the start of the experiment, counts of colony forming unit (cfu) of mesophilic bacteria ranged from 2.2 to 4.8 log cfu, counts of psychrotrophic bacteria ranged from 2.5 to 3.4. Srikar et al (1993) pointed out that the growth of halophilic bacteria might have been favoured by the high salt concentrations in the products. Halophile counts changed signi®cantly (P < 0.001) depending on storage temperature and salt concentrations.…”
Section: Time (Days)mentioning
confidence: 99%